Pengaruh Intensitas Aset Biologis, Kepemilikan Manajerial, dan Ukuran Perusahaan terhadap Pengungkapan Aset Biologis pada Perusahaan Agrikultur di Indeks Saham Syariah Indonesia (ISSI) - Kesturi, Dea Noverya; Fitri, Ainul; Rahman, Taufiqur (Jurnal Akuntansi Terapan dan Bisnis, 2025)
This study aims to analyze the effect of Biological Asset Intensity, Managerial Ownership, and Company Size on the disclosure of biological assets in agricultural companies listed on the ISSI for the period 2020–2024. Using purposive sampling, eight companies were selected as samples, and secondary data from annual reports were analyzed using panel data regression with a Random Effect Model. The results show that Biological Asset Intensity and Company Size have a negative and significant effect on biological asset disclosure, while Managerial Ownership has a positive and significant effect; all three variables are also proven to have a significant simultaneous effect. These findings indicate that the transparency of biological asset disclosure in agricultural companies in ISSI is more influenced by agency mechanisms through managerial ownership, while company size and high biological asset intensity have not effectively encouraged compliance with PSAK 69.